1999
DOI: 10.1111/j.1699-0463.1999.tb01573.x
|View full text |Cite
|
Sign up to set email alerts
|

Detection of clinical vancomycin‐resistant enterococci in Denmark by multiplex PCR and sandwich hybridization

Abstract: Since the first cases of human infection with vancomycin‐resistant enterococci (VRE) were reported in the late eighties, there has been a dramatic increase in VRE all over the world. So far, there have not been any reports of clinical VRE in Denmark. In this study we have investigated 131 clinically important enterococci sent to Statens Serum Institut from all over Denmark during the period July 1995 to May 1997. The susceptibility to vancomycin, teicoplanin, ampicillin and gentamicin was tested by the agar di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
9
0

Year Published

1999
1999
2019
2019

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(9 citation statements)
references
References 19 publications
0
9
0
Order By: Relevance
“…Specificity was very high. A few other studies reported PCR assays with 100% sensitivity (253,260). The discrepancies between these studies may reflect differences in the number of isolates tested, the type of sample used, and the need to carefully control the composition of multiplex PCR incubations.…”
Section: Detection Of Resistancementioning
confidence: 79%
“…Specificity was very high. A few other studies reported PCR assays with 100% sensitivity (253,260). The discrepancies between these studies may reflect differences in the number of isolates tested, the type of sample used, and the need to carefully control the composition of multiplex PCR incubations.…”
Section: Detection Of Resistancementioning
confidence: 79%
“…For instance, in order to improve gene identification, PCR is often followed by an additional hybridisation step with internal probes such as routinely performed in the Danish surveillance programme of clinical Vanomycin-resistant enterococci (VRE) isolates [51]. In other procedures the PCR protocol has been adapted to improve sensitivity and/or specificity in which the initial PCR is followed by a second PCR using a primer combination located within the amplified fragment.…”
Section: Pcr-based Detection Of Antibiotic Resistance Genesmentioning
confidence: 99%
“…We have found two VanA-and three VanB-positive isolates by phenotypic susceptibility tests; by multiplex PCR the two vanApositive and only 1 of 3 vanB-positive strains were identified (Table 1). Also, the second set of primers (31) failed to amplify the same two vanB-positive strains. Notwithstanding the fact that the alignment of the chosen primers shows no mismatch with the published sequences, the vanB primers may fail to amplify some vanB genes because of variability of the sequences in the primer regions (16,29).…”
mentioning
confidence: 99%
“…It has been succesfully used to identify vancomycin-resistant enterococci (8,13,18,21,22,25,26,30,31), but it may also be used broadly to identify all enterococci; nevertheless, this approach certainly fails to identify some enterococcal species outside the reach of the primers, and for this reason it is also necessary to include among the proposed molecular methods for enterococcal species identification the amplification and sequencing of the 16S ribosomal DNA (rDNA) gene (25,28,38). Two hundred seventy-nine clinical strains consecutively identified as enterococci by three hospital laboratories in Rome were studied ( Table 1 All strains submitted as glycopeptide resistant were verified with the E-test method (AB BIODISK, Solna, Sweden) in our laboratory.…”
mentioning
confidence: 99%